The optimization of T6 heat treatment on microstructure and mechanical properties of thixoformed LM4 aluminium alloy - Safian, Mohd Azizul Hikmi (UTeM, 2018)
Thixoforming process is an attractive process that produces near net shape product with complex geometry. This process also produces lightweight parts that would reduce fuel consumption while maintaining their good mechanical properties. In this work, LM4 (light metal) aluminium alloys is used due to its low density among metals, high specific energy, good specific strength, high wear and high corrosion resistance. Thixoforming consists of three main processes that are thixotropic feedstock production, reheating and forming. The feedstock material for thixoforming was produced through cooling slope casting under argon gas atmosphere. Thixotropic feedstock is cast using cooling slope (CS) casting technique by pouring at 660 °C at 45 ° tilt angle with 400 mm slope length. The grains size and the shape factor is identified using the Image-J software. Differential scanning calorimetry (DSC) test is used to determine the heat flow and liquid fraction profile of LM4 aluminium alloy before thixoforming. The feedstock is then reheated in the induction furnace and heated up to their semisolid temperature at 580 °C (50 % of liquid content) followed by forming process by using vertical hydraulic press. After the thixoforming process, T6 heat treatment is conducted towards the thixoformed LM4 aluminium alloy with various combination of solution treatment (ST) and ageing temperature and time. The solution treatment is conducted at 510 °C to 530 °C for 30 min, 60 min and 120 min respectively followed by quenching and ageing at 160 °C to 180 °C for 2 hours, 4 hours and 6 hours respectively. Microstructure and phase formation were analysed using an optical microscope, scanning electron microscopy and X-ray diffraction while mechanical properties, coefficient of friction (CoF) and corrosion rate (CR) were obtained from hardness and tensile tests, wear test and corrosion test respectively. The result indicates that the solution treatment at 530 °C for 30 min, quenching in water and followed by ageing at 180 °C for 2 hours resulted in increased of the mechanical properties, wear resistance and corrosion resistance. The tensile strength, surface hardness, coefficient of friction and corrosion resistance of the thixoformed heat treated alloys is increased up to 252.387 MPa, 98.9 HV, 0.4259, 0.0102 mmpy respectively as compared to the thixoformed sample 184.526 MPa, 88.9 HV, 0.4321 and 0.0165 mmpy respectively. The microstructures of the T6 heat treated samples showed a spheroidization of eutectic silicon and the intermetallic phase Al2Cu, β-Al5FeSi and Al5Cu2Mg8Si6 were distributed homogenously in the sample. Based on the analysis, the new T6 heat treatment schedule with the solution treatment of 30 minutes showed a significant effect to increase the mechanical properties of the thixoformed alloys.